2016
DOI: 10.3892/or.2016.4676
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA miR-93-5p regulates expression of IL-8 and VEGF in neuroblastoma SK-N-AS cells

Abstract: Abstract. The role of the microRNA miR-93-5p on the secretome profile and the expression levels of vascular endothelial growth factor (VEGF) and interleukin-8 (IL-8) was investigated in the neuroblastoma SK-N-AS cell line by Bio-Plex analysis and RT-qPCR. The results indicate that VEGF and IL-8 are the major miR-93-5p molecular targets. This conclusion was based on in vitro transfection with pre-miR-93-5p and anti-miR-93-5p; these treatments inversely modulated both VEGF and IL-8 gene expression and protein re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(33 citation statements)
references
References 41 publications
1
32
0
Order By: Relevance
“…These findings pointed out the co-expression relationship between AK131850 and VEGFa. Recently, Fabbri et al has predicted the binding sites of miR-93-5p in the 3’UTR region of VEGF and found that miR-93-5p may be proposed to reduce VEGF dependent angiogenesis in neuroblastomas [54]. Similarly, our results also predicted the putative miR-93-5p binding sites with 3′-UTR of VEGFa and luciferase reporter assay further confirmed that miR-95-5p directly targeted VEGFa.…”
Section: Discussionsupporting
confidence: 72%
“…These findings pointed out the co-expression relationship between AK131850 and VEGFa. Recently, Fabbri et al has predicted the binding sites of miR-93-5p in the 3’UTR region of VEGF and found that miR-93-5p may be proposed to reduce VEGF dependent angiogenesis in neuroblastomas [54]. Similarly, our results also predicted the putative miR-93-5p binding sites with 3′-UTR of VEGFa and luciferase reporter assay further confirmed that miR-95-5p directly targeted VEGFa.…”
Section: Discussionsupporting
confidence: 72%
“…A study showed that miR‐93 represses angiogenesis and the growth of colorectal cancer by down‐regulating erb‐b2 receptor tyrosine kinase 2 (ERBB2), p21, CCNB1 and VEGF expression 126. In neuroblastoma, miR‐93 represses IL‐8‐ and VEGF‐dependent angiogenesis by targeting IL‐8 and VEGF mRNAs 127. In addition, miR‐93 reduces angiogenesis in human lymphatic endothelial cells (HLECs) by reducing angiopoietin 2 (Ang 2) expression by directly binding to the 3′UTR of the Ang 2 gene 128.…”
Section: Mirnas Regulated By Pro‐or Anti‐angiogenesis Factors or Hypomentioning
confidence: 99%
“…and VEGF mRNAs. 127 In addition, miR-93 reduces angiogenesis in human lymphatic endothelial cells (HLECs) by reducing angiopoietin 2 (Ang 2) expression by directly binding to the 3 0 UTR of the Ang 2 gene. 128 Taken together, miR-93 has dual effects on angiogenesis in different tissues and cells via multiple molecular mechanisms.…”
Section: Mir-93mentioning
confidence: 99%
“…Therefore, the random effect model was selected. The overall sensitivity, specificity, positive likelihood ratio (PLR), negative likelihood ratio (NLR), diagnostic odds ratio (DOR), and AUC were 0.76 (0.64-0.85), 0.82 (0.64-0.92), 4.2 (2.2-8.1), 0.29 (0.22-0.40), 14 (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25), and 0.85 (0.82-0.88), respectively, suggesting the excellent potential diagnostic capability of miR-93 in various human cancers. Subgroup analyses based on ethnicity, sample type, and expression level were performed ( Table 2).…”
Section: The Diagnostic Meta-analysismentioning
confidence: 99%